PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATERI COMPUTATIONAL THINKING MATA PELAJARAN INFORMATIKA KELAS VII SMP - Fernando, Erik; Novrianti; Pratiwi, Rahmi; Masriani, Elsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research and development (R&D) study aimed to produce an interactive multimedia learning media using Scratch 3.0 on the Computational Thinking topic for Grade VII students at SMP Negeri 15 Padang. The development model employed was the 4D model (Define, Design, Develop, Disseminate) proposed by Thiagarajan et al. (1974). The interactive multimedia integrates text, images, animations, audio, and interactive quizzes to provide an engaging, student-centered learning experience. Validity assessment was conducted by one subject matter expert (content validity 92.85%, very Valid) and two media experts (media validity 97.5% and 98.75%, both very Valid). Practicality testing involving 31 Grade VII students yielded an overall score of 91.5% (very Practical). These results demonstrate that the interactive multimedia developed is both valid and practical for use in Informatika learning, particularly for improving students’ Computational Thinking skills through algorithmic and visual programming experiences.